Рух сільськогосподарських матеріалів нахиленою робочою поверхнею - Кухарець, С. М.; Пінкін, А. А.; Ярош, Я. Д.; Kukharets, S.; Pinkin, А.; Yarosh, Y. (КНТУ, 2016)
В статті знайдено рівняння руху частинки сільськогосподарського матеріалу нахиленою робочою поверхнею із врахуванням коефіцієнтів опору, що відчуває частинка при русі. Подальші дослідження необхідно спрямувати на встановлення коефіцієнту опору для різних видів сільськогосподарських матеріалів та обґрунтування динаміки зміни коефіцієнту тертя експериментальним чи теоретичним шляхом. The paper found the equation of motion of agricultural material particles on the inclined working surface, taking into account the resistance coefficient of the particle raw material in motion. Mathematical models of the movement of agricultural raw materials particles play an important role in the design and specific parameters of the working process of many agricultural machines. The equations of motion of agricultural materials worktops are needed as in the operation of the existing machines as well as in the design of new ones. Equations are tailored to gravity and drag forces acting on the particle. Further research should be directed to the installation of the drag coefficient for different types of agricultural materials and study the dynamics of change in friction coefficient experimentally or theoretically.
The movement of agricultural materials on an inclined working surface
Keywords: частинка; сировина; рух; тертя; опір; поверхня; particle feed movement; friction resistance; surface